Physico-Chemical Studies of Effluent in Sanganer Area - Bishnoi, Om Prakash (International Journal of Pharmaceutical & Biological Archive, 2017)
The Physico-chemical study was made in industrial Sanganer area to assess the quality of effluent, soil quality, and effects of effluent on crop plants. The samples were alkaline besides having high chemical oxygen demand. They had more than the permissible concentrations of heavy metals like copper, zinc, lead, chromium, and manganese. These industries also caused an adverse impact on its surrounding flora, fauna, and residents.